Deep rivers of learning. (March 2018) - Claxton, Guy
It's all too easy for teachers to focus on building students' knowledge and skills without paying attention to the mental habits that students need to be effective learners. Guy Claxton discusses the need for teachers to design their instruction in a way that promotes resilience, curiosity, independence, and a positive disposition toward learning .